2022
DOI: 10.18174/sesmo.18074
|View full text |Cite
|
Sign up to set email alerts
|

Containerization for creating reusable model code

Abstract: Will you be able to run your computational models in the future? Even with well-documented code, this can be difficult due to changes in the software frameworks and operating systems that your code was built on. In this paper we discuss the use of containers to preserve code and their software dependencies to reproduce simulation results in the future. Containers are standalone lightweight packages of the original model software and their dependencies that can be run independent of the platform. As such they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As described in [23], modularity is an important design principle for software design. Concepts such as Docker images also have shown that modularity often comes along with reusability [24]. 4) Self-Descriptive: It should be self-describing in the sense that the components using the API provide information about their functionality and how to use them.…”
Section: A Requirementsmentioning
confidence: 99%
“…As described in [23], modularity is an important design principle for software design. Concepts such as Docker images also have shown that modularity often comes along with reusability [24]. 4) Self-Descriptive: It should be self-describing in the sense that the components using the API provide information about their functionality and how to use them.…”
Section: A Requirementsmentioning
confidence: 99%